Effects of training in pairs versus training alone on reaching proficiency in minimally invasive Roux-en-Y-gastric bypass on a virtual reality trainer in medical students: a randomized-controlled trial - Cizmic, Amila; Reichert, Paulina; Häberle, Frida; Preukschas, Anas; Pianka, Frank; Mehrabi, Arianeb; Nießen, Anna; Müller, Beat P.; Hackert, Thilo; Grotelüschen, Rainer; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2025)
Minimally invasive surgery (MIS) is the standard approach in bariatric surgery. The most common bariatric procedures are sleeve gastrectomy and Roux-en-Y-Gastric Bypass (RYGB). Simulation training, including virtual reality (VR), is useful when learning MIS. Training in pairs has proven beneficial in acquiring basic MIS skills. However, this has not been tested on more complex procedures such as MIS RYGB. The study aimed to assess the learning effects of training MIS RYGB on a VR trainer in pairs compared to solo training.